UPAYA KBRI MANILA DALAM PEMBEBASAN WNI DARI PENYANDERAAN KELOMPOK ABU SAYYAF - Indah Pratikasari; Sri Muryantini (Jurnal Studi Diplomasi dan Keamanan, 2017)
This paper discusses the efforts of the Embassy of the Republic of Indonesia in Manila in the release of Indonesian crew members who were held hostage by the Abu Sayyaf group during 2016. It applies the negotiation theory which is one of the diplomatic functions performed to provide Service and protection of Indonesian citizens abroad. The data used in analyzing this thesis take a lot of source which come from direct interview with Minister Counselor of Political Affairs of Indonesian Embassy in Manila in Philippines and also reports, books, newspapers and various sources from internet. This paper concludes that the policies made and carried out by the Government of Indonesia and the Indonesian Embassy in Manila in performing its role as RI Representative in the Philippines in order to free the Indonesian crew members who were taken hostage by the Abu Sayyaf group in the South Philippines region. However, in the process of acquittal, an intensive negotiation process is needed both with the Philippine government and with the Abu Sayyaf using the negotiation strategy in order to achieve a win-win solution without having to use weapons or pay ration in the form of money demanded by the hostage taker.